Pengaruh Diameter Inner-Helical Fin Terhadap Characteristic of Performance Counter Flow Heat Exchanger - Bula, Muhamad; Wahyudi, Slamet; Hamidi, Nurkholis (Rekayasa Mesin, 2010)
The study of energy conservation using the head exchanger with different fin shapes havebeen carried out, including research on the counter flow heat exchanger using a helical spiral shaped fin is placed on the inner pipe. The problem lies in the acquisition of the influence of the diameter of the helical fin to the characteristic of performance counter flow heat exchanger. The diameter of the helical fin which the test is 8 mm, 12 mm and 16 mm. The objective is achieved, the effect of the diameter of the helical fin characteristic of performance counter flow heat exchanger in the increase of hot water discharge 400 liters / hour, 500 liters / hour, 600 liters /hour, 700 liters / hour, 800 liters / hr and 900 liters / hour. Method of design of experiments with laboratory-scale experiments using a set-up equipment double tube heat exchanger is the method used. The results obtained, the highest effectiveness for all types of helical fins foundon discharge 400 liters / h with the order from highest to lower the effectiveness of internal diameter of 12 mm reached 17.66%, diameter of 8 mm effectiveness reaches 15:56% and the internal diameter of 16 mm effectiveness of achieving 14.29%. For the plain tube efektiftasobtained 11:48%.Keywords : heat exchanger, the diameter of the helical fin, hot water discharge, effectiveness